Implementation of Permendagri Policy No. 70 of 2019 concerning Local Government Information Systems (SIPD) at the Bone Bolango Regency Health Office - Kariyani Tangahu; Salma Rivani Luawo; Muh Firyal Akbar; Apris A.Tilome (Universitas Muhammadiyah Palu, 2026)
The purpose of this study is to determine the implementation of the policy of the Minister of Home Affairs No. 70 of 2019 concerning the Regional Government Information System (SIPD) at the Bone Bolango Regency Health Office. This study uses a qualitative research method with a descriptive approach. Data collection techniques use observation, interviews and documentation studies. The indicators used in this study have 4 aspects, namely 1) communication, 2) resources, 3) disposition, and 4) organizational structure. The results of the study show that the implementation of SIPD has not been optimal. This is due to several factors, including the limitation of competent human resources in the field of information technology, lack of technical training, internet network constraints, and lack of maximum support for facilities and infrastructure. In addition, coordination between work units also needs to be improved to support better data integration. Therefore, the government must improve infrastructure to support the implementation of policies, such as strengthening the SIPD network and servers. Then conduct training on human resources and improve facilities and infrastructure.